Note - A. C.
1940-11-17 013-0051-001 17.xii.40 MR. BOLTON. I translated the attached letter for the I.F.T.U. It confirms that Caballero was in unoccupied Southern France when he was handed over to the Franco Government. That was where Llopez was when he wrote to Araquistain. The reference to "Uncle Paco" is to be taken to mean Caballero. A.C. 292/946/13/51(i)